EXPLORING THE RELATIONSHIP BETWEEN MALADAPTIVE DAYDREAMING AND CREATIVE WRITING PRODUCTIVITY - Pranoto, Yohanes Heri; Angel Seanita (Esteem Journal of English Education Study Programme, 2025)
This study explores the relationship between maladaptive daydreaming and creative writing performance among students in the English Language Education Program at Musi Charitas Catholic University. Using a quantitative correlational method with total sampling, data were gathered through two questionnaires distributed to all students. The findings reveal a significant positive correlation between daydreaming and creative writing, indicating that while daydreaming can inspire creativity and ideas, it may also hinder focus and academic performance. Students acknowledged daydreaming as a source of relaxation and creative thought, yet emphasized the need to manage it during lessons to remain productive. The study highlights the dual role of daydreaming both beneficial and disruptive in academic settings. It suggests that educators can harness its creative potential by incorporating structured writing tasks that align with students’ imaginative thinking. A balanced approach, combining creativity with focus, is essential for maximizing student engagement and well-being. This research offers unique insight into how maladaptive daydreaming influences English education students’ writing skills and provides practical considerations for integrating this phenomenon into classroom practice.